SensorQuad The Flying Sensor Platform for Teaching - Novak, M. (IECON 2021 – 47th Annual Conference of the IEEE Industrial Electronics Society, 2021)
The SensorQuad is designed as a low cost teaching platform for embedded programming. It focuses on students of mechanical engineering, especially in the field of automation, that need to understand the concepts of control systems. It allows to show the basics, then develop the skills further for example with DC motor control, sensor communication, to more advanced topics such as for example PID control. It uses an STM32 processor, four DC motors, LEDs and several sensors (acceleration, magnetic field, temperature, humidity,...). Commented examples are provided to students to shown how to work with the peripherals. It is designed as a low cost device, so that the student can eventually buy it and use it at home as well. It is also provided with an example application for Android so that the programming of a control interface and bidirectional Bluetooth communication can be shown as well.